2018
DOI: 10.1002/mp.12798
|View full text |Cite
|
Sign up to set email alerts
|

Texture analysis of T1‐w and T2‐w MR images allows a quantitative evaluation of radiation‐induced changes of internal obturator muscles after radiotherapy for prostate cancer

Abstract: Texture analysis applied on T1-w and T2-w MR images has demonstrated its ability in quantitative evaluating radiation-induced changes in obturator muscles after PCa radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Some of these features have been also reported as predictive of treatment response in esophageal cancer, 36 able in differentiating prostate cancer aggressiveness 37 or able in characterizing structural modifications induced by RT in normal tissues. 23 Other studies focused on the reproducibility of T2w-MRI radiomic features in the prostate using different scanners, 20,24 and, among the considered features families, GLCM was the most reproducible and with higher ability in discriminating tumor and nontumor regions. Duron et al 26 found that the method used for image discretization has a major impact on the stability of MRI features and that the adoption of a fixed bin-width is preferable to the fixed bin number.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some of these features have been also reported as predictive of treatment response in esophageal cancer, 36 able in differentiating prostate cancer aggressiveness 37 or able in characterizing structural modifications induced by RT in normal tissues. 23 Other studies focused on the reproducibility of T2w-MRI radiomic features in the prostate using different scanners, 20,24 and, among the considered features families, GLCM was the most reproducible and with higher ability in discriminating tumor and nontumor regions. Duron et al 26 found that the method used for image discretization has a major impact on the stability of MRI features and that the adoption of a fixed bin-width is preferable to the fixed bin number.…”
Section: Discussionmentioning
confidence: 99%
“…A more detailed description of the image registration and contour propagation procedure can be found in previous works. 23,28…”
Section: B Roi Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…ΔIntensity and Δ95th percentile showed an upward trend with the dose, and the Gray‐level Co‐occurrence Matrix (ΔGLCM)‐contrast showed a decreasing trend with the dose. It is an imaging level reflection of the physiological structure change 30 …”
Section: Application Of Radiomics In Radiotherapymentioning
confidence: 99%